Mutations of Pre-mRNA Splicing Regulatory Elements: Are Predictions Moving Forward to Clinical Diagnostics - Grodecká, Lucie; Buratti, Emanuele; Freiberger, Tomáš (International journal of molecular sciences, 2017)
For more than three decades, researchers have known that consensus splice sites alone are not sufficient regulatory elements to provide complex splicing regulation. Other regulators, so-called splicing regulatory elements (SREs) are needed. Most importantly, their sequence variants often underlie the development of various human disorders. However, due to their variable location and high degeneracy, these regulatory sequences are also very difficult to recognize and predict. Many different approaches aiming to identify SREs have been tried, often leading to the development of in silico prediction tools. While these tools were initially expected to be helpful to identify splicing-affecting mutations in genetic diagnostics, we are still quite far from meeting this goal. In fact, most of these tools are not able to accurately discern the SRE-affecting pathological variants from those not affecting splicing. Nonetheless, several recent evaluations have given appealing results (namely for EX-SKIP, ESRseq and Hexplorer predictors). In this review, we aim to summarize the history of the different approaches to SRE prediction, and provide additional validation of these tools based on patients' clinical data. Finally, we evaluate their usefulness for diagnostic settings and discuss the challenges that have yet to be met.
Keywords: mutace; prekurzory RNA; RNA Splice Sites; lidé; Genetic Diseases, Inborn; Molecular Diagnostic Techniques; RNA Precursors; diagnostické techniky molekulární; genetické nemoci vrozené; místa sestřihu RNA; Mutation; Humans